Management and clinical outcome of concomitant pulmonary embolism and paradoxical saddle aortic arch embolism. Issue 8 (28th August 2019) - Mancuso, Enrico; Winterbottom, Andrew Philip; Boyle, Jonathan R; Hildebrand, Diane R
Abstract : A 65-year-old man presented in a peri-arrest situation after collapse, he was found hypoxic with ischaemic arms. CT imaging showed massive bilateral pulmonary embolisms (PEs) and an aortic arch embolus extending from brachiocephalic trunk to left subclavian artery. Following intravenous thrombolysis, repeat imaging revealed that the aortic embolus had migrated distally into both axillary arteries and had occluded the right carotid from origin to skull base. Bilateral upper limb embolectomies were carried out from the brachial arteries together with forearm fasciotomies. Left hemianopia related to a right middle cerebral artery territory infarct was managed conservatively; forearm fasciotomy wounds were primarily closed and the patient was discharged on lifelong anticoagulation. A transoesophageal echocardiogram revealed a patent foramen ovale. This case demonstrates a very unusual presentation of concomitant PE and paradoxical saddle aortic arch embolism. A multidisciplinary approach has resulted in an excellent clinical outcome for this complex patient.